Creep and Electrochemical Corrosion Behavior of Heat-treated Mg-9Al-1Zn Alloy - Ravi Naldi; Anawati - Anawati (Journal of Engineering and Technological Sciences, 2020)
The high-strength Mg-9Al-1Zn alloy has been extensively investigated due to its potential application as a structural material in the automotive industry. The main challenges for its use are the low creep and corrosion resistance. In this work, heat treatment at 415 °C for 2 h was conducted on as-cast Mg-9Al-1Zn to improve its creep resistance. The corrosion behavior of the alloy was studied by the electrochemical method in an NaCl solution. The creep test results under 66.5 MPa load at 200 °C indicated one order of magnitude higher creep resistance of the heat-treated alloy relative to the as-cast one. The heat-treated specimen was ruptured after 6.5 h while the as-cast one was ruptured within 0.6 h. Creep occurred locally following the Î² phase in the alloy as evident from the cavities observed after the test. Reduction in the density of the discontinuous Î² precipitates resulting from heat treatment of the alloy lowered the susceptibility to creep. The smaller volume fraction of Î² precipitates suppressed the cathodic reaction during the polarization test and raised the electrochemical impedance spectra during the EIS test. The heat treatment improved not only the creep resistance but also the corrosion resistance of the Mg-9Al-1Zn alloy.